The real McCoy the life of an African American inventor - Towle, Wendy; Clay, Wil (New York Scholastic, 1993)
A biography of the Canadian-born black American who studied engineering in Scotland and patented over fifty inventions despite the obstacles he faced because of his race
Hurg
5
Keywords: African American inventors -- Biography; African Americans -- Biography; Inventors